High hemoglobin glycation index is associated with increased systemic arterial stiffness independent of hyperglycemia in real-world Japanese population: A cross-sectional study. (September 2020) - Nagayama, Daiji; Watanabe, Yasuhiro; Yamaguchi, Takashi; Saiki, Atsuhito; Shirai, Kohji; Tatsuno, Ichiro
Aims: To investigate the association of metabolic parameters including hemoglobin glycation index (HGI, observed HbA1c – predicted HbA1c) with systemic arterial stiffness assessed by cardio-ankle vascular index (CAVI). Subjects: We analyzed the cross-sectional data from 22, 696 subjects (mean age 48.0 years, mean FPG 88 mg/dL, mean HbA1c 5.5%) with or without past history of metabolic disorders including diabetes. Results: Men had higher body mass index (BMI), CAVI, blood pressure (BP), FPG, HbA1c, total cholesterol and triglyceride; and lower age, HGI and HDL-cholesterol. After stratifying subjects into HGI quartiles, the highest quartile (Q4) group showed higher age, female ratio, and frequencies of obesity, hypertension, diabetes, and dyslipidemia. Furthermore, bivariate logistic regression model revealed that the Q4 of HGI was a significant predictor of high CAVI (⩾9.0) independent of the presence of diabetes. Conclusion: High HGI is associated with systemic arterial stiffening independent of hyperglycemia. This index is therefore expected to be not only a predictor of hypoglycemia, but also a therapeutic guide for atherosclerosis.